2020
DOI: 10.18295/squmj.2020.20.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Disparity among Endocrinologists and Gynaecologists in the Diagnosis of Polycystic Ovarian Syndrome

Abstract: Objectives: This study aimed to compare endocrinologists’ versus gynaecologists’ approaches in using the Rotterdam criteria to diagnose polycystic ovarian syndrome (PCOS). Methods: This cross-sectional study was conducted at Physiology Department, King Saud University, Riyadh, Saudi Arabia, between December 2017 and April 2018. A validated self-administered questionnaire in English was used to obtain information from endocrinologists and gynaecologists regarding their approaches to diagnosing PCOS. Each group’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In a small survey study out of Saudi Arabia, endocrinologists reported greater reliance on hyperandrogenism and gynecologists more frequently used ultrasound in application of the Rotterdam criteria. 45 A large physician survey ( n = 1,318) out of China examined the implementation of metabolic screening recommendations from the 2018 International PCOS Guideline in general obstetrician–gynecologists (85.8%) and reproductive endocrinologists (14.2%). 46 Despite their low representation in this sample, reproductive endocrinologists were significantly more likely to order oral glucose tolerance test and lipid testing and prescribe metformin in patients with fertility demands.…”
Section: Resultsmentioning
confidence: 99%
“…In a small survey study out of Saudi Arabia, endocrinologists reported greater reliance on hyperandrogenism and gynecologists more frequently used ultrasound in application of the Rotterdam criteria. 45 A large physician survey ( n = 1,318) out of China examined the implementation of metabolic screening recommendations from the 2018 International PCOS Guideline in general obstetrician–gynecologists (85.8%) and reproductive endocrinologists (14.2%). 46 Despite their low representation in this sample, reproductive endocrinologists were significantly more likely to order oral glucose tolerance test and lipid testing and prescribe metformin in patients with fertility demands.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, a comparison between endocrinologists and gynecologists was not the primary objective of the present study, and it has been specifically addressed in previous studies. [22][23][24] Other limitations include introducing a selection bias as only those interested in PCOS could have attempted the survey. It is worth noting that the low response rate may have been attributed to the study period, which coincided with the initial outbreak of the coronavirus disease 2019 pandemic and the generally reduced attention to research activities beyond the pandemic Furthermore, the wide difference in the responses concerning the ultrasound criteria can be attributed to the potential phrasing ambiguity in identifying PCO morphology by ultrasound by transabdominal versus transvaginal approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the responses were from the Arabian Gulf (64.7%), followed by the rest of the Middle East (18.4%) and North Africa (10.5%) (►Table 1). However, most of the responses were from four countries: Saudi Arabia (59), Qatar (33), Iraq (33), and the United Arab Emirates (22). This was followed in decreasing order by Egypt (7), Sudan (6), South Africa (5), Libya (5), Bahrain (4), Nigeria (3), Lebanon (2), Morocco (2), Oman (2), Kenya (2), Kuwait (2), Mali (1), Uganda (1), and Zimbabwe (1).…”
Section: General Characteristics Of the Respondentsmentioning
confidence: 99%
“…24 Studies have documented differences in the diagnosis of PCOS among physicians with different experiences. 25 Our study focuses on the factors of patient turnover of physicians, aiming to find the influence on the ability of doctors. Through comprehensive evaluation of diagnosis and treatment capacity, we can find and narrow the disparities, and promote the overall improvement of the medical level.…”
mentioning
confidence: 99%